Climate adaptation law and policy in the United States - Craig, Robin Kundis (Frontiers in Marine Science, 2022)
When President Biden took office in January 2021, he immediately re-invigorated the United States’ commitment to addressing climate change, including climate adaptation, through Executive Order 13990—Protecting Public Health and the Environment and Restoring Science To Tackle the Climate Crisis (January 20, 2021) and Executive Order 14008—Tackling the Climate Crisis at Home and Abroad (January 27, 2021). Federal agencies have continued to implement these and other climate-related executive orders. This article examines recent legal developments to summarize the United States’ current policy approach to climate change adaptation, especially as such developments affect marine sector. Despite the natural tendency to focus on the federal government—and there have indeed been improvements in federal adaptation policy since the Biden Administration took office—this article also argues that focusing solely on the federal government reveals only one facet of important developments in the United States’ climate adaptation policy. Instead, this article acknowledges and illuminates the pluralistic and federalistic structure of United States governance, concluding that much climate adaptation work occurs within tribes and through state and local governments, regardless of who sits in the Oval Office.